Odi et amo: discursive strategies and ambiguity in the narratives of violence - Poppi, Fabio Indio Massimo (European journal of criminology, 2021)
Ambiguity plays a central role in how narratives about violence are told, but research has rarely taken into account the ambiguity used by criminals with complex motives. Drawing on narrative criminology, this contribution explores how ambiguity is deployed in the stories of violence publicly told in a television interview by Mario Mariolini, a paraphiliac Italian killer sentenced for homicide. The analysis of the narratives, in tandem with the discursive strategies therein, demonstrates that ambiguity is strategically used for different purposes. As a result, we identify three central narratives, each displaying different ways of making instrumental use of ambiguity. In contrast to the analysis of the ambiguity produced by ordinary criminals, this contribution shows how particular and severe criminal cases are better suited for the study of narratives about violence because of the more complex interplay between the ideological and communicative dimensions.